2005
DOI: 10.1897/04-566r.1
|View full text |Cite
|
Sign up to set email alerts
|

Bioconcentration of persistent organic pollutants in four species of marine phytoplankton

Abstract: The uptake of polychlorinated biphenyls (PCBs) was studied in four species of marine algae. A novel experimental system to establish and maintain constant dissolved concentrations of PCBs was employed. Headspace sampling was used to verify that the freely dissolved concentrations remained constant with time. The headspace analysis also allowed sorption to dissolved organic carbon (DOC) to be quantified for all but the most lipophilic PCB congeners. Equilibration with the dissolved phase was rapid for three of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 32 publications
2
34
1
Order By: Relevance
“…Clearly, a calibration time of 60 d, a time duration often used in fish exposure experiments [5][6][7], can yield reasonable accuracy when C w is determined with the laboratory-calibrated C pe /C w . We previously obtained a curvilinear relationship between the logarithm of PDMS-water partition coefficient (log K f ) and log K OW for PCBs with the turning point at log K OW approximately equal to 7 to 7.5 [17,18], which is similar to the fieldobserved correlations between log-based bioconcentration factor and log K OW [19][20][21]. This curvilinearity was attributed to the difference in the Gibbs free energies for cavity formation in PDMS and octanol that can become significant for larger molecules [18].…”
Section: Sorption Kinetics Of Target Bde Congenerssupporting
confidence: 66%
“…Clearly, a calibration time of 60 d, a time duration often used in fish exposure experiments [5][6][7], can yield reasonable accuracy when C w is determined with the laboratory-calibrated C pe /C w . We previously obtained a curvilinear relationship between the logarithm of PDMS-water partition coefficient (log K f ) and log K OW for PCBs with the turning point at log K OW approximately equal to 7 to 7.5 [17,18], which is similar to the fieldobserved correlations between log-based bioconcentration factor and log K OW [19][20][21]. This curvilinearity was attributed to the difference in the Gibbs free energies for cavity formation in PDMS and octanol that can become significant for larger molecules [18].…”
Section: Sorption Kinetics Of Target Bde Congenerssupporting
confidence: 66%
“…Maroli et al, 1993;Micheli et al, 1995;Pavoni et al, 2003), as well as three reports of other persistent organic pollutants (POPs) being taken up by algae from water over time. Gerofke et al (2005) looked at the uptake of 20 PCB congeners in water by 4 species of marine phytoplankton and found that in three of them a maximum rate was reached in less than 24 h. Cruz-Uribe et al (2007) measured the uptake and metabolism of the explosive compound TNT from water in one green and two red seaweed. At a TNT concentration of 10 mg L À1 , the two red seaweeds removed approximately 80% of the TNT in the first 48 h while the green removed approximately 50%.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the lipid-normalized BAF for microalgae was a linear function of Kow with a slope close to 1 when log Kow < 6. Meanwhile, the lipid-normalized BAF was less than Kow when log Kow > 6 (Stange & Swackhamer 1994, Gerofke et al 2005. If there is equilibrium between the hydrophobic organic chemicals partitioning the water and cell lipids, the linear relationship between BAF and Kow exists when log Kow is close to 7 (Swackhamer & Skoglund 1993).…”
Section: Discussionmentioning
confidence: 99%